Analisis Minat Mahasiswa dalam menggunakan e-learning dengan mengintegrasikan TAM dan IDT - Ika Arthalia Wulandari; Guna Yanti Kemala Sari Siregar; Muhammad Ihsan Dacholfany (Jurnal Komtika (Komputasi dan Informatika), 2022)
Through e-learning students are encouraged to learn from their homes individually and not in groups as in traditional learning where there are classes and study groups. This gives students the opportunity to organize their time according to their preferences as they attend individual online courses in their homes. They also have the freedom to choose the online courses that they find useful for them and their needs. This study aims to explore and examine the factors that influence the behavioral intention of students to use e-learning. The relationship between TAM variables and Innovation Diffusion Theory is integrated and explored to answer this goal. This research was conducted on 238 students of Muhammadiyah Metro University as active e-learning users. The findings show that of the 13 hypotheses developed, there are 4 that were rejected. It was found that there was no effect between Relative Advantage and Perceived Usefulness, Perceived Compatibility on Perceived Usefulness, Relative Advantage on Perceived Easy of Use, and between Perceived Easy of Use and Perceived Usefulness.